Pengaruh Pelatihan, Gaya Kepemimpinan, dan Kompensasi Terhadap Produktivitas Dengan Kinerja Pegawai Sebagai Mediasi pada UMKM yang Berada di Desa Wisata Kasongan Daerah Istimewa Yogyakarta - Rochmad Bayu Utomo; Sundjoto; Anita Kartika Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia have experienced a significant increase, but productivity has not increased, one of which is Kasongan Tourism Village which is famous for its Pottery MSMEs, the number of craftsmen has decreased, one of the consequences of the order-based system. This study examines three groups of questions: 1) how training, leadership style, and compensation have a positive effect on employee performance; 2) how training, leadership style, compensation, and employee performance have a positive effect on productivity; and 3) how training, leadership style, and compensation affect productivity. The population of this study was all workers as craftsmen in Kasongan Tourism Village, totaling 43 employees who as craftsmen data came from Kasongan Village. The sampling technique used saturated samples. Analysis tools This study uses descriptive analysis techniques and quantitative analysis techniques with a structural equation model or Structural Equation Modeling (SEM), especially Partial Least Square (PLS). The results of this study 1) Training does not affect employee performance, while leadership style and compensation have a positive effect on employee performance; 2) Training, leadership style and compensation partially do not affect productivity, while performance affects productivity; 3) Employee performance does not mediate the relationship between training and productivity, while employee performance mediates the relationship between leadership style and compensation and productivity.